Effects of leadership competencies on students’ learning outcomes as mediated by organisational culture in selected Saudi higher education institutions / Radwan, Omaymah Abdulwahab A - Radwan, Omaymah Abdulwahab A (2020)
Higher education institutions (HEIs) play a significant role in increasing the social and economic growth of a nation. They are responsible for the grooming of qualified individuals from various academic disciplines to meet the needs of the community. Thus, HEIs are in dire need of competent leadership that can help them to contribute to the nation’s development, and to achieve the desired learning outcomes among students. Previous studies indicated that leadership has both direct and indirect impacts on students’ learning outcomes (SLOs). By utilising mediating components in the educational environment, some studies have established the positive impact leaders can exert on students. Other studies pointed out that organisational culture could be one of the mediator components that impact positively on the outcomes of the educational environment. However, most of these studies were mainly conducted at basic education, such as among kindergarten and 12 years of basic education. There is still a lack of studies that examine the effect of leadership competencies of academic leaders on SLOs in HEIs. There is also limited evidence on the mediation role that organisational culture plays in HEIs. Therefore, this study aims to examine the effect of leadership competencies of academic leaders on SLOs in selected Saudi HEIs. It also aims to examine the mediating effect of organisational culture on the effect and relationship between leadership competencies of academic leaders and SLOs in selected Saudi HEIs. It also aims to identify the level of academic leadership competencies, the type of organisational culture, and the level of SLOs in selected Saudi HEIs. It also aims to examine the effect of organisational culture on SLOs in selected Saudi HEIs. Hence, this study utilised a quantitative research design by distributing questionnaires consisting of 120 items to faculty members in selected Saudi HEIs. They were selected using a proportionate stratified random sampling technique. A total of 496 responses were received, and the data were analysed using SPSS (V.23) and PLS-SEM. The findings indicated that there are an indirect effect and relationship between leadership competencies of academic leaders and SLOs in selected Saudi HEIs. The findings illustrated that organisational culture mediated the effect and relationship between leadership competencies of academic leaders and SLOs in the selected Saudi HEIs. The findings indicated that academic leaders have a very high level of competencies in terms of their personal skills and required skills. The findings also stated that Clan Culture is the type of culture that is being practised currently in selected Saudi HEIs. The results also showed that students in selected Saudi HEIs at a high level of learning outcomes. The findings also pointed out that the organisational culture has a significant and direct effect on SLOs in selected Saudi HEIs. The findings of the study highlighted the importance of organisational culture in HEIs to the policymakers, stakeholders, and practitioners so that they will incorporate it in the future direction and planning of HEIs. The study has the potential to reflect positively on the performance of HEIs and the Ministry of Education.